Hotel and IT decision-maker characteristics and information technology adoption relationship in the hotel industry. (12th August 2014) - Bulent Ozturk, Ahmet; Hancer, Murat
Abstract : Purpose: – The purpose of this paper is to investigate the impact of hotel property characteristics and information technology (IT) decision-maker characteristics on radio frequency identification (RFID) technology adoption in the hotel industry. Design/methodology/approach: – The data of the study were collected using the subscription list of Hospitality Financial and Technology Professionals (HFTP). A Web survey was used to collect the data of the study. An email invitation was sent out to invite the entire list of HFTP subscribers (3, 080) to participate in the survey. Approximately 3, 000 emails were delivered and 154 questionnaires were returned. Of 154 questionnaires, 125 were used in the study for further analyses. Analysis of variance (ANOVA) was used to determine whether hotel property characteristics (property size and chain affiliation) and IT decision-maker characteristics (age, education level and job tenure) differed on intention to adopt RFID technology. Findings: – ANOVA results indicated that there were significant differences on intention to adopt RFID technology by property size and chain affiliation, IT decision-makers' age, education level and job tenure. The results indicated that larger hotels and hotels that are part of a franchise are more likely to adopt RFID technology. In addition, IT decision-makers who are young, with high level of education and with shorter job tenure are more likely to adopt RFID technology. Originality/value: – RFID technology is one of the recent technologies that gained great attention from the hotel operators in recent years. This study is one of the first studies in the hotel industry that provides valuable information to technology vendors for identifying potential RFID technology adopters in the hotel industry.